Application of Problem Based Learning Model to Enhance Student Learning Outcomes Science Elementary School Fifth Grade 145 Pekanbaru - Zaini, Rika Zaini Rika; Alpusari, Mahmud Alpusari Mahmud; H. Lazim N, H. Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The background of this research is the lack of science learning outcomes of students, with an average grade 64.28 while the value of minimum completeness criteria (KKM) IPA is 70. Among the students who totaled 28 people only 11 students who achieve 39 KKM with classical completeness, 28 % . This study is a Class Action Research (CAR), which aimed to improve learning outcomes fifth grade science students of SD Negeri 145 Pekanbaru by applying Problem Based Learning Model. Formulation of the problem: Is the Problem Based Learning Model Application to Improve Student Learning Outcomes Science Elementary School Fifth Grade 145 Pekanbaru